Compatibility study between paracetamol and pharmaceutical excipients used in liquid dosage forms - Haris @ Harith, Muhammad Salahuddin; Mohamed, Farahidah; Doolaanea, Abd Almonem; Mohd Shafri, Mohd Affendi (2016)
Differential scanning calorimetry (DSC) and attenuated total reflectance (ATR) infrared spectroscopy methods were used to investigate the compatibility between an active pharmaceutical ingredients (API), paracetamol (PCM), with excipients such as honey, xanthan gum, sodium methylparaben, sodium propylparaben and sodium citrate. To assess the possible interactions between PCM and other excipients, the melting point of individual PCM was compared to the melting point of binary mixtures PCM and excipients (physical mixing of PCM:excipient of 1:1 ratio). DSC curve showed a sharp endothermic peak at 170.8°C corresponding to the PCM melting point (literature value: 169◦C - 172◦C). The melting points of PCM remained similar for all PCM binary mixtures except for PCM-sodium methylparaben and PCM-sodium propylparaben binary mixtures where disappearance of PCM melting points were exhibited by the thermogram. ATR infrared spectroscopy was used to support and assist the interpretation of DSC findings. On the basis of ATR supportive infrared spectra, incompatibilities between PCM and other excipients were not detected.